Technostress at the University: How does it affect job satisfaction? - Nia Ariyani Erlin; Hendrik Heri Sandi; Mefid, Khairen Niza (Universitas Negeri Padang, 2024)
Digitalization and performance efficiency are currently enforced in all fields, including in higher education. Universitas Negeri Padang as one of the universities in Indonesia also does not stop doing digital transformation and efficiency. In addition to the implementation of e-learning and hybrid lectures, UNP has just released the MyUNP application and the SIMTA application. This requires users to quickly adapt to this new application. On the other hand, lecturers and education personnel are also still trying to adapt to previously released applications such as sister, e-performance, rumah gadang, and so on. This study aims to see how the level of stress caused by technology or known as technostress on lecturers and education personnel then will also see how it affects job satisfaction. This study had 37 respondents and was analyzed using SPSS and SEM-PLS analysis tools. Conducted at the end of the year which is a deadline for various tasks and workloads, this time was chosen to be able to more accurately record the level of technostress felt by respondents. The results of this study show that three dimensions of technostress have a negative effect on job satisfaction but there are two dimensions of technostress that can have a positive effect on job satisfaction. Further discussion of the results and suggestions for future research are discussed.